MS-150-10-f02-003: Letter from W. Lawley? - Lawley, W. (Valdosta, GA: Valdosta State University Archives and Special Collections, 1893)
Letter from W. Lawley?. On stationary printed with: Telegraph Station Beaconsfield/Railway Station/Wooburn Green/Hall Barn, Beaconsfield, Bucks [Envelope matching stationary from L. Northbrook [Thomas George Baring] dated August 17, 1893; signature does not match
1 handwritten letter and envelope, 2 pages.
Keywords: Personal correspondence; Letters; Poets--Correspondence; Arnold, Edwin, Sir, 1832-1904